2023
DOI: 10.3390/ma16031285
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing of Metal–Diamond Composites with High-Strength CoCrCuxFeNi High-Entropy Alloy Used as a Binder

Abstract: This paper focuses on the study of the structure and mechanical properties of CoCrCuxFeNi high-entropy alloys and their adhesion to single diamond crystals. CoCrCuxFeNi alloys were manufactured by the powder metallurgy route, specifically via mechanical alloying of elemental powders, followed by hot pressing. The addition of copper led to the formation of a dual-phase FCC + FCC2 structure. The CoCrCu0.5FeNi alloy exhibited the highest ultimate tensile strength (1080 MPa). Reductions in the ductility of the CoC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The value of 5ATO-7, 5ATO-8, and 5ATO-9 is 1.609R, while that of 5ATO-10, 5ATO-11, and 5ATO-12 is 1.560R. Rost et al found that the formation of a high-entropy solid solution was affected by the molar fraction of cations, and indicated that the configuration entropy was an important driving force for the formation of a single phase [ 3 ]. According to the concept of high entropy, the value should be higher than 1.609R [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of 5ATO-7, 5ATO-8, and 5ATO-9 is 1.609R, while that of 5ATO-10, 5ATO-11, and 5ATO-12 is 1.560R. Rost et al found that the formation of a high-entropy solid solution was affected by the molar fraction of cations, and indicated that the configuration entropy was an important driving force for the formation of a single phase [ 3 ]. According to the concept of high entropy, the value should be higher than 1.609R [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since 2004, the research into high-entropy alloys (HEAs) has received great attention due to their vast compositional space and has shown remarkable physical (magnetic and conductivity) and mechanical (strength, hardness and wear resistance) properties [ 1 , 2 , 3 ]. The HEAs were defined as multi-component alloys which were formed by five or more elements with equal or close to equal atomic fractions [ 1 ].…”
Section: Introductionmentioning
confidence: 99%